(untitled) (Scientific journal of the Fergana State University, 2024)
Among the functional-semantic types of speech, discussion speech differs from other types of speech in terms of compositional construction. In many scientific sources, the discussion speech is mainly divided into three parts. Which: thesis, evidence and conclusion. This scientific article presents scientific hypotheses about the compositional construction of this type of speech.